2021
DOI: 10.1002/anie.202103808
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Co‐Conversion of CH4 and CO2 Mediated by Rhodium–Titanium Oxide Anions RhTiO2

Abstract: Catalytic co‐conversion of methane with carbon dioxide to produce syngas (2 H 2 +2 CO) involves complicated elementary steps and almost all the elementary reactions are performed at the same high temperature conditions in practical thermocatalysis. Here, we demonstrate by mass spectrometric experiments that RhTiO 2 − promotes the co‐conversion of CH 4 and CO 2 to free 2 H 2 +CO and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…We grow and cut Ni-doped CeBr 3 single crystal into substrates with ad iameter of 2cma nd then transform them into PSC Ni x Ce 1Àx O 2 with the identical dimensions in 99 %Ar/ 1%O 2 atmosphere at 620-720 8 8Cu sing lattice reconstruction strategy.T he CeBr 3 and NiBr 2 are pretty sensitive to oxygen and water, which therefore requires that we treat them in glove box with N 2 atmosphere.T he PSC Ni x Ce 1Àx O 2 shows % 68 %p orosity in the porous architectures.F igure 1a shows the XRD patterns of PSC Ni-doped CeO 2 monoliths with an optical image in the inset with the facets of ( 200) and (220), respectively,which are grown from the Ni-doped CeBr 3 single crystals with the facet of (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and (0002), respectively.The peak of the (200) plane of PSC Ce 1Àx Ni x O 2 shifts slightly to higher angle (from 33.3608 8 to 33.3968 8)i nc omparison with pure PSC CeO 2 in Figure S1, indicating nominal variation in lattice constant upon doping with Ni ions.T he lattice constants are found to be 5.3674 and 5.3618 for PSC CeO 2 and PSC Ce 1Àx Ni x O 2 ,r espectively.A nd the volume of the unit cell is obtained as 158.042 and 157.981 3 for PSC CeO 2 and PSC Ce 1Àx Ni x O 2 ,r espectively.T he above analysis thus confirms that Ni ions occupy the Ce site in the lattice in the form of dopant, leading to as olid solution without observing the formation of impurity phase like NiO.Figure S2 and Figure S3 show the schematic of the crystal growth from Ni-doped CeBr 3 to Ni-doped CeO 2 .T he lattice mismatch between Ni-doped CeBr 3 with the facet of (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and (0002)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We grow and cut Ni-doped CeBr 3 single crystal into substrates with ad iameter of 2cma nd then transform them into PSC Ni x Ce 1Àx O 2 with the identical dimensions in 99 %Ar/ 1%O 2 atmosphere at 620-720 8 8Cu sing lattice reconstruction strategy.T he CeBr 3 and NiBr 2 are pretty sensitive to oxygen and water, which therefore requires that we treat them in glove box with N 2 atmosphere.T he PSC Ni x Ce 1Àx O 2 shows % 68 %p orosity in the porous architectures.F igure 1a shows the XRD patterns of PSC Ni-doped CeO 2 monoliths with an optical image in the inset with the facets of ( 200) and (220), respectively,which are grown from the Ni-doped CeBr 3 single crystals with the facet of (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and (0002), respectively.The peak of the (200) plane of PSC Ce 1Àx Ni x O 2 shifts slightly to higher angle (from 33.3608 8 to 33.3968 8)i nc omparison with pure PSC CeO 2 in Figure S1, indicating nominal variation in lattice constant upon doping with Ni ions.T he lattice constants are found to be 5.3674 and 5.3618 for PSC CeO 2 and PSC Ce 1Àx Ni x O 2 ,r espectively.A nd the volume of the unit cell is obtained as 158.042 and 157.981 3 for PSC CeO 2 and PSC Ce 1Àx Ni x O 2 ,r espectively.T he above analysis thus confirms that Ni ions occupy the Ce site in the lattice in the form of dopant, leading to as olid solution without observing the formation of impurity phase like NiO.Figure S2 and Figure S3 show the schematic of the crystal growth from Ni-doped CeBr 3 to Ni-doped CeO 2 .T he lattice mismatch between Ni-doped CeBr 3 with the facet of (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and (0002)…”
Section: Resultsmentioning
confidence: 99%
“…[11] Therefore,t he huge gap between surface/interface science and actual operation conditions is difficult to bridge in the DRM reactions.I ti sg enerally accepted that the limited availability and high prices of DRM catalysts based on noble metals (Pt, Pd, Rh, Ru), although highly active for this reaction, have restricted their large-scale applications in industry. [12,13] Low-cost Ni catalyst dispersed on oxide supports could overcome the above limitations and have received appreciable attention. [14] However, Ni-based catalysts could be problematic especially owing to the high temperature of operation or rapid deactivation due to the chemical poisoning (C or Od eposition) and nanoparticle sintering at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks marked with asteriskes are due to secondary reactions with CH 4 and CO 2 or water impurity. Reproduced with permission [32b] . Copyright 2021, Wiley‐VCH.…”
Section: Conversion Of Ch4 With Co2 and H2omentioning
confidence: 99%
“…Very recently, by replacing the VO x support with a titanium oxide cluster, it was found that the RhTiO 2 − with a single Rh atom could also mediate catalytic DRM reaction to produce syngas [32b] . A mass spectrometer coupled with a double ion trap system containing two QMFs and two LIT reactors was employed to characterize the elementary reactions.…”
Section: Conversion Of Ch4 With Co2 and H2omentioning
confidence: 99%
“…In particular, methanation reactions have widely received a lot of attention [ 4 , 5 ] as the generated synthetic natural gas can effectively relieve pressure on natural gas supplies [ 6 , 7 ]. Methanation catalysts are often based on Group VIII metals (e.g., Ru [ 8 , 9 , 10 ], Rh [ 11 ], Co [ 12 , 13 ], Fe [ 14 , 15 ], Ni [ 16 , 17 ]) that are supported on various oxide supports. Among the active metals used in methanation reactions, precious metals such as Ru and Rh are the most reactive and selective, but their relatively high cost makes them at the disadvantage economically.…”
Section: Introductionmentioning
confidence: 99%